Pathway enrichment analysis of differential metabolites, highlighting significantly impacted metabolic pathways and associated enrichment statistics based on KEGG or other pathway databases. - Ji-Xin Zhao (22056386) (2025)
Pathway enrichment analysis of differential metabolites, highlighting significantly impacted metabolic pathways and associated enrichment statistics based on KEGG or other pathway databases.